Upaya Peningkatan Penjualan Melalui Strategi Labeling Usaha Keripik Tempe di Desa Glonggong - Nova Titin Lestari; Husna Ni'matul Ulya (Abdimas Indonesian Journal, 2021)
This community service program activity aims to identify internal and external factors contained in a business, formulate alternative strategies that can be applied in developing a tempe chips business in Glonggong Village, Dolopo District, Madiun Regency, considering that tempeh chips are a favorite food for the community. This research method is an ABCD (Asset Based Community-Driven Development) approach, with the steps taken are inculturation, discovery, design, define, and reflection. The strategies used to increase sales of tempe chips business in Glonggong Village, Dolopo District, Madiun Regency are: (1) Improving packaging to increase consumer attractiveness (2) Providing product labels on tempe chip packaging (3) Expanding marketing networks by utilizing information and communication technology on line. After this service activity was carried out, the tempe chips business experienced an increase in sales after having a new product label so as to increase the welfare of members and increase business income.